Molecular characterisation of the clonal emergence of high-level ciprofloxacin-monoresistant Haemophilus influenzae in the Region of Southern Denmark. (June 2016) - Fuursted, Kurt; Hartmeyer, Gitte Nyvang; Stegger, Marc; Andersen, Paal Skytt; Justesen, Ulrik Stenz
Highlights: We report the appearance of high-level ciprofloxacin-resistant Haemophilus influenzae in the Region of Southern Denmark. The strains were non-encapsulated, biotype III and were demonstrated by whole-genome sequencing to be clonal belonging to a single clade with an unknown MLST type (double-locus variant of ST196). The strains were monoresistant to ciprofloxacin with an MIC >32 mg/L. The resistome revealed both previously characterised and novel putative resistance-related mutations in gyrA, parC and parE . No epidemiological link between the patients could be demonstrated, but isolates (although multiresistant) with an identical MLST profile and mutations in the QRDR have recently been reported in Spain. Abstract: Haemophilus influenzae is an important human pathogen usually susceptible to quinolones. Here we report the emergence of high-level ciprofloxacin-monoresistant H. influenzae in the Region of Southern Denmark. Four isolates were collected for phenotypic and molecular characterisation using whole-genome sequencing (WGS). During an 18-month period, the occurrence of high-level ciprofloxacin-monoresistant H. influenzae in patients aged 1–77 years from sputum, ear and eye samples was detected. An epidemiological link between the patients could not be identified. The isolates were non-encapsulated, biotype III and were demonstrated by WGS to be clonal belonging to a single clade with an unknown multilocus sequence type (double-locus variant of ST196). The antibiogram demonstrated that they were all monoresistant to ciprofloxacin with a minimum inhibitory concentration (MIC) >32 mg/L. In silico resistome analysis revealed identical, both previously characterised and novel, putative resistance-related mutations in gyrA (S84L and D88 N), parC (K20R, S84I, D356A or T356A, and M481I) and parE (E151 K, I159A, D420 N and S599A) in all isolates. The isolates were otherwise negative for any resistance genes. This is the first description of the clonal emergence of high-level monoresistant H. influenzae due to amino acid substitutions in gyrA, parC and parE.